Over 100 years of Krapina: New insights into the Neanderthal thorax from the study of rib cross-sectional morphology. Issue 122 (September 2018) - García-Martínez, Daniel; Radovčić, Davorka; Radovčić, Jakov; Cofran, Zachary; Rosas, Antonio; Bastir, Markus
Abstract: The Krapina costal sample was studied by Gorjanović-Kramberger in the early twentieth century. He pointed out unique features in the sample such as the rounder rib cross-section, which was recently confirmed in other Neanderthal specimens. Round rib cross-sections are characteristic of Homo ergaster, suggesting this may be plesiomorphic for Pleistocene Homo, but it is unknown whether Homo antecessor also had this rib shape. Furthermore, the influence of allometry on the cross-sectional shape of ribs is still unknown. The large costal sample from Krapina allows us to address these issues. We quantified cross-section morphology at the midshaft throughout a closed curve of one landmark and nine sliding semilandmarks in the Krapina costal remains ( n  = 7), as well as in other Neanderthals ( n  = 50), H. antecessor ( n  = 3) and modern humans, both fossil ( n  = 12) and recent ( n  = 160). We used principal components analysis and mean comparisons to explore interspecific differences, regression analysis to investigate allometry, and partial least squares analysis to examine covariation of cross-section shape and overall rib morphology. Neanderthal cross-sections tended to be larger than those of recent humans except for the Krapina and Tabun remains. Regarding shape, inter-group differences were found only in the diaphragmatic thorax, where Neanderthal and H. antecessor ribs were statistically significantly rounder than those of modern humans. Allometry accounted for covariation of size on shape, but the Neandertal and modern human trajectories had different slopes. While our results based on the Krapina costal sample are similar to previous findings, we also make several new insights: 1) the cross-section morphology observed in Neanderthals was probably present in H. antecessor, albeit less marked; 2) the distinct roundness of Neanderthal cross-sections is not related to size; 3) rounder cross-sections are correlated with ribs presenting less curvature in cranial view and a low degree of torsion in recent humans. These results are important for the interpretation of fragmentary Neanderthal costal remains, and the fact that the differences are marked only in the diaphragmatic thorax could have implications for breathing kinematics.